Dictionary of development banking : a compilation of terms in English, French and German with definitions in English - Wohlers-Scharf, Traute; Shetty, Chandrashekar Majur (Amsterdam ; New York : Elsevier Pub. Co., 1972)
This compilation incorporates over 1200 term. These are organized under three broad sections: the environmental frame; development banking; and development bank.
Includes index.
ne 24/08/2021
Ref.
Keywords: Development banks; English language